The health psychology: a multidisciplinary approach about stress and behavioral change - Moscoso, Manolete S. (1994)
This article reviews research and professional trends in the field of health psychology and behavioral medicine. I also discuss recent research on stress, immune system, behavioral change and health promotion. An increasing focus on the human immunodeficiencyvirus (HN/AIDS) is very important given the Rde of health psychology in terms of prevencing further spread of the epidemic and in maintaining a good qualiry of life. I examined psychosocial and immune system stress responses in individuals before and after their nocification of HN status andas a consequence of stress management intervention procedures. Psychological and social factors in the development of illness are considered.